Manajemen Pembelajaran dalam Meningkatkan Mutu Pendidikan - Amiruddin Siahaan; Rizki Akmalia; Muhammad Irvan Marsya; Bunga Br Lubis; Nindi Aulia Putri; Ansari Fahmi (Departement of Mathematics Education, 2023)
Learning management is a process of managing, which includes planning, organizing, controlling (directing), and evaluating activities related to the process of teaching students by including various factors in it, in order to achieve educational goals and seek to improve the quality of education. Quality education is education that is able to produce graduates with good morals. And to produce students who have good morals, good learning management is also needed. This study aims to determine the application of learning management to improve the quality of education. This research uses descriptive qualitative research methods. The method used to collect data is through observation, interviews, and documentation. Observations are used to obtain data or descriptions of geographical locations, facilities and infrastructure, the condition of teachers and students. Interviews were used to obtain data about learning management. Documentation is used to obtain data on historical reviews and organizational structures. The process of data analysis in this study used an interactive model analysis which consisted of: data reduction, data presentation, and drawing conclusions. From the results of the study it was shown that: 1. The learning management process went well, with the implementation of learning in accordance with proper planning and organization. has been determined. 2. The quality standards of education that are applied continue to increase.